2020
DOI: 10.1186/s13018-020-01756-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a potential gene target for osteoarthritis based on bioinformatics analyses

Abstract: Background: Osteoarthritis (OA) is the most common chronic joint disease worldwide. It is characterized by pain and limited mobility in the affected joints and may even cause disability. Effective clinical options for its prevention and treatment are still unavailable. This study aimed to identify differences in gene signatures between tissue samples from OA and normal knee joints and to explore potential gene targets for OA. Methods: Five gene datasets, namely GSE55457, GSE55235, GSE12021, GSE10575, and GSE19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hu Y et al [ 32 ] screened three hub genes (CX3CR1, MYC, and TLR7) and identified potential drugs for the treatment of OA. Duan ZX et al [ 33 ] not only identified PTHLH as the most relevant gene for OA but also further tested and determined PTHLH levels in the plasma and synovial fluid of knee joints of OA patients. In our study, based on the FerrDb database and GEO dataset, the hub gene SLC3A2 was screened, and its function was verified by a series of cellular experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Hu Y et al [ 32 ] screened three hub genes (CX3CR1, MYC, and TLR7) and identified potential drugs for the treatment of OA. Duan ZX et al [ 33 ] not only identified PTHLH as the most relevant gene for OA but also further tested and determined PTHLH levels in the plasma and synovial fluid of knee joints of OA patients. In our study, based on the FerrDb database and GEO dataset, the hub gene SLC3A2 was screened, and its function was verified by a series of cellular experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we downloaded the data with accession numbers GSE12021, GSE55235, 26 and GSE55457. 27 The samples included in our study were sourced from Homo sapiens.…”
Section: Methodsmentioning
confidence: 99%
“…Mice primary chondrocytes were isolated and cultured as previously reported (Duan et al, 2020). In brief, cartilage tissues from the mice were cut into small pieces under sterile conditions.…”
Section: Isolation and Culture Of Chondrocytes From Tibial And Verteb...mentioning
confidence: 99%